(untitled) (Third Sector Social Economic Review, 2025)
This study aims to analyze how Occupational Future Time Perspective (OFTP) varies across demographic variables. OFTP refers to individuals’ perceptions of their remaining time in the workplace and how these perceptions influence their career goals, motivation, and behaviors. The research was conducted with 334 marketing and sales employees working in various sectors in the province of Artvin. Data were collected using the OFTP scale developed by Zacher and Frese (2009) and adapted into Turkish. The data were analyzed through independent samples t-tests and one-way ANOVA. The study examined the three subdimensions of OFTP focus on opportunities, focus on limitations, and perceived remaining time across participants’ gender, age, marital status, and tenure. The findings revealed that significant differences emerged only in the “perceived remaining time” dimension. Younger, single, and less tenured employees perceived that they had more time left in their careers compared to their older, married, and more experienced counterparts. In contrast, no statistically significant differences were found in the dimensions of focus on opportunities or focus on limitations based on demographic variables. The results indicate that individuals’ perceptions of occupational time are shaped by age, social roles, and organizational experience, suggesting that human resource strategies should consider these demographic factors in career planning and development.